Do Cigarette Smoking and Obesity Affect Semen Abnormality in Idiopathic Infertile Males? - Lee, Hui Dai (Korean Society for Sexual Medicine and Andrology, 2014)
PURPOSE: This study was conducted to find the relative risk of semen abnormality with respect to smoking history and obesity. MATERIALS AND METHODS: Subfertile or infertile men were enrolled in this study from July 2010 to June 2011. All participants provided their cigarette use information, self-reported weight, height, semen analysis, physical examination, and sexually transmitted disease status. None of the enrolled patients had any specific pathological reason for infertility. Semen abnormality was defined as a condition in which one or more parameters did not satisfy the World Health Organization's criteria. RESULTS: A total of 1,073 male patients were considered for this study. After the application of the inclusion criteria, 193 patients were finally analyzed. These patients were divided into two groups according to semen abnormality: the normal semen group (n=72) and the abnormal semen group (n=121). Baseline characteristics, except age and smoking history, were not significantly different between the two groups. Smoking history and age were risk factors for the semen abnormality of idiopathic infertile male patients. CONCLUSIONS: Smoking and old age were risk factors for semen abnormality. However, obesity did not affect the semen abnormality. Smoking affected semen quality and is therefore expected to play a negative role in conception.